Numerical modeling of Dnepr river water pollution after emergency leakage from the ammonia pipe "Tolyatti – Odessa" - Pshinko, O. M.; Amelina, L. V.; Bilyaev, M. M. (Science and Transport Progress, 2010)
The 2D numerical model was developed and used to simulate river pollution after accident on the ammonia pipe over Dnipro River. The model is based on the numerical integration of the K-gradient transport model and potential flow. The results of numerical experiment are presented.